Solid Grounding / Framing Movement: extending community opportunity in an urban park. Raw vs refined - Bacon, Joanna (School of Architecture, Planning and Geomatics, 2017)
This dissertation follows a process of research and design. The project research is defined in the first section of the dissertation as a conceptual duality of raw vs refined. The study of a raw heavy materiality of architecture, in comparison to a delicate refined light weight architecture, where a link is developed presenting light, experience and embodiment of materials as the common denominators. The design is then developed and revealed throughout the next section. The final outcome of this project is a Resource Centre (carved into and added onto the park) to facilitate after hours' life of school children in Woodstock, Cape Town, chosen to actively involve and integrate the community with the park. The year began with a group investigation into a section cut through Cape Town. Starting at Devils Peak, moving down through District 6 and Woodstock, ending at the harbour. This presented a rich base of knowledge for this particular strip of land. Although my individual study was into rock – the upper portion of the valley section, I chose Trafalgar park as my site. It was chosen for its rich historical value and positioning in the city, with beautiful views of the main geological landmarks in Cape Town, namely Table Mountain, Lions Head, Signal hill and the ocean. The focal point and what drew me to this site was the solidity of exposed rock seen in the remnants of the 18th century defence system in the form of a redoubt. With old trees hinting at the existence of this wall, marking either side of exactly where it used to lie. The surrounding land forms a beautiful parkscape with many changing levels presenting great opportunity for intervention. Frequent visits to site allowed me to understand how the park and neighbourhood functioned, and how people used, or rather, underused the park in its existing state.